Perinatal outcomes of reduced fetal movements: a cohort study. Issue 1 (December 2016) - McCarthy, Claire; Meaney, S.; O'Donoghue, K.
Abstract Background The perception of reduced fetal movement (RFM) is an important marker of fetal wellbeing and is associated with poor perinatal outcome (such as intra-uterine death). Methods We conducted a prospective study of women presenting with RFM over 28 weeks' gestation to a tertiary-level maternity hospital. We examined pregnancy outcomes and compared them to a retrospectively collected control group delivering contemporaneously. Results In total, 275 presentations were analysed in the RFM group, with 264 in the control group. Women with RFM were more likely to be nulliparous (p = 0.002) and have an induction of labour (p = 0.0011). 26.5 % (n = 73) of cases were admitted following presentation with RFM, and 79.4 % (n = 58) delivered on primary presentation. Overall, 15.2 % (n = 42) women were induced for RFM specifically. Conclusion This prospective study shows the increased burden of care required by those with RFM, including increased neonatal unit admission rates, increased induction rates and higher surveillance demands, demonstrating the need for increased attention to this area of practice.